Using non-equilibrium state in the MoO3 -H-C system for low temperature synthesis of ultradispersed molybdenum carbide powders - M.P. Savyak; I.V. Uvarova; T.M. Yarmola (Processing and Application of Ceramics, 2008)
Pd additives and atomic hydrogen can accelerate kinetic processes in molybdenum reduction from molybdenum trioxide with hydrogen at 350°C in the presence of carbon. Such a low temperature reduction process (starting temperature 300–350°C) promotes the formation of a thermodynamically unstable nanodispersed phase with the specific surface area of 280 m2/g, which may be related to the formation of the intermediate cubic molybdenum suboxide Mo1-xO, responsible for the preservation of the MoO3 faceting. The specific surface area of 280 m2/g corresponds to the particle size ~3 nm. The phase transformation leading to the formation of Mo2C in the MoO3-Pd-H2-C system at a relatively low temperature (650°C) is the result of relaxation of the high free energy in the thermodynamically unstable system. The carbide formation process at such a low temperature yields carbide with the specific surface area from 4 to 40 m2/g (depending on the carbide-forming component), which can be easy sintered. The morphology of this carbide inherits the faceting of the initial whiskerous trioxide molybdenum. The microhardness of the sintered samples is significantly higher than that of carbide produced traditionally at high temperature.